2004
DOI: 10.1128/aac.48.6.2124-2131.2004
|View full text |Cite
|
Sign up to set email alerts
|

Application of Real-Time Quantitative PCR to Molecular Analysis of Candida albicans Strains Exhibiting Reduced Susceptibility to Azoles

Abstract: Real-time quantitative PCR was used to measure expression levels of genes encoding efflux pumps, ERG11 and two control genes, ACT1 and PMA1, in a collection of 14 fluconazole-susceptible Candida albicans isolates. For each gene, average expression levels and variations within the population were determined. These values were then used as reference points to make predictions about the molecular basis of resistance in 38 clinical isolates (the majority of which were resistant to fluconazole) obtained from 18 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
169
1
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(177 citation statements)
references
References 18 publications
(20 reference statements)
1
169
1
6
Order By: Relevance
“…This is consistent with the predominant resistance mechanisms seen with these species. Posaconazole is known to bind more extensively to the target enzyme, 14␣-demethylase, of C. albicans than does fluconazole, due in part to the presence of a long hydrophobic side chain that serves to stabilize the binding of posaconazole to the target, making it less susceptible to the effect of point mutations in the ERG11 gene (3,50). Indeed, Li et al (17) demonstrated that isolates of C. albicans, from a patient with OPC, that were resistant to fluconazole and voriconazole but susceptible to posaconazole all had the same five missense mutations in ERG11 that specifically reduced the binding of fluconazole and voriconazole to the target enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the predominant resistance mechanisms seen with these species. Posaconazole is known to bind more extensively to the target enzyme, 14␣-demethylase, of C. albicans than does fluconazole, due in part to the presence of a long hydrophobic side chain that serves to stabilize the binding of posaconazole to the target, making it less susceptible to the effect of point mutations in the ERG11 gene (3,50). Indeed, Li et al (17) demonstrated that isolates of C. albicans, from a patient with OPC, that were resistant to fluconazole and voriconazole but susceptible to posaconazole all had the same five missense mutations in ERG11 that specifically reduced the binding of fluconazole and voriconazole to the target enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have demonstrated strain-level discrimination for automated rep-PCR with the DiversiLab system, including mycobacteria (2) and fungi of both Aspergillus (15) and Candida spp. (3,23). The medical and economic benefit of a highly integrated, comprehensive infection control program that includes routine genotyping has been previously demonstrated (14).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of strain level differentiation, too few strains, and no strains that were clonal, were incorporated for comparison; therefore no conclusions can be drawn about its utility for strain typing fungi (8). At least two studies report the utility of the DiversiLab system for typing Candida albicans strains that have developed resistance to azoles, but the studies were not designed to compare rep-PCR to other techniques (4,10). Finally, in an analysis of both outbreak-and non-outbreak-associated Neisseria meningitidis isolates of various serogroups, the DiversiLab system had excellent serogroup and strain level discrimination (9).…”
Section: Discussionmentioning
confidence: 99%